Influence of Patient’s Satisfaction towards Continuance Usage Intention of Online Teleconsultation Application - Caroline Widjaja; Hendra Achmadi (Budapest International Research and Critics University, 2022)
Patients start to shift from offline consultation to online teleconsultation to maintain their health. This Study was conducted to analyze what factors influence patient satisfaction and the continuance usage intention of teleconsultation applications. This study uses a quantitative method, by taking primary data of 160 primary data from patients that have an experience on mobile teleconsultation application (Halodoc) in this Covid-19 pandemic situation, and distributed using google form. The data analysis is using PLS-SEM to test whether there is a high correlation between factors or not. After knowing the components that affect patient satisfaction, the results shows that Patient Satisfaction has a major effect on Continuance Usage Intention, which is 0.684 and can also be seen from R2 of Continuance Usage Intention which is 0.661, that means a Moderate Predictive Accuracy. So, it can be concluded that Patient Satisfaction has a strong influence on Continuance Usage Intention of patients who are using a mobile teleconsultation application during this